Analisis Penilaian Sikap Religius Mahasiswa di Universitas Adzkia dan UIN Mahmud Yunus Batusangkar - Muspardi, Muspardi; Yusmanila, Yusmanila; Aisyah, Siti; Effendi, Heri; Lelfita, Lelfita; Nurpatri, Yeni (Journal of Civic Education, 2024)
This research aims to analyze students' religious attitude assessments in Universitas Adzkia and UIN Mahmud Yunus Batusangkar. The methods used in this research include preliminary studies, data collection via google forms questionnaires, interviews, and documentation studies. The data obtained was analyzed qualitatively and quantitatively. The research results show that integrating religious attitudes in the higher education curriculum is a strategic step that can improve the quality of graduates both in academic aspects and moral integrity. This research also found that assessing religious attitudes at the higher education level helps students understand and apply religious values in everyday life, as well as reducing negative behavior and increasing positive behavior. The implication of this research is the need for a holistic approach in fostering student religiosity, including strengthening spiritual formation programs, providing worship facilities, and mentoring programs. Regular evaluation of the religiosity development program is also recommended to ensure its effectiveness in meeting student needs and challenges.